Statistical analysis of electric field perturbations in ELF based on the CSES observation data before the earthquake - Zhang, Fu-Zhi; Huang, Jian-Ping; Li, Zhong; Shen, Xu-Hui; Li, Wen-Jing; Wang, Qiao; Zeren, Zhima; Liu, Jin-Lai; Li, Zong-Yu; Chen, Zhao-Yang (Frontiers in Earth Science, 2023)
To explore the correlation between earthquakes and the pre-earthquake ionospheric shallow frequency (ELF) electric field perturbations phenomenon, the paper investigated the pre-earthquake ionospheric perturbations phenomenon, and then the Spatio-temporal evolution characteristics of the electromagnetic field before and after the global Ms ≥6.0 strong earthquakes from 2019 to 2021 were statistically analyzed. In this paper, the power spectrum data of the ELF (19.5–250 Hz) band of ionospheric electric field observed by the China Seismo-Electromagnetic Satellite (CSES) electric field detector are preclinically processed by the C-value method. A stable background field observation model was constructed using the data from 75 to 45 days before the earthquake observed by the CSES in the range of 15° above the epicenter. Then, the amplitude of the spatial electric field disturbance over the epicenter relative to the background field is extracted. Finally, the superposition analysis method statistically analyzes the spatial and temporal evolution of the spatial electric field before and after the earthquake with different characteristics. The statistical results show that the anomalies first appear in the fourth period (15–19 days before the earthquake) and the third period (10–14 days before the earthquake) and then reach the most vital and most evident during the pro-earthquake period (4 days before the earthquake and the day of the earthquake); In terms of the intensity of the anomalies caused, the magnitude seven earthquakes are stronger than the magnitude 6.0–7.0 earthquakes, and marine earthquakes are stronger than land earthquakes; in terms of the ease of observing the anomalies, the magnitude 7.0 and above are more accessible to observe than the magnitude 6.0–7.0 earthquakes, and marine earthquakes are more accessible to observe than land earthquakes.